2018
DOI: 10.1016/j.ress.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk impact of completion time changes combining PSA and DSA model insight and human reliability analysis

Abstract: Highlights  Evaluation risk impact of completion time changes  Combination of deterministic and probabilistic model  Identification of unknown accident sequences using thermo-hydraulic simulations  Increasing human error probability accuracy through best estimate codes  More realistic PSA model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Cheng et al (2018) [128] examined the combined issue of condition-based maintenance, quality control, and production lot size for an imperfect production system that is vulnerable to degradation in both reliability and quality. Using a probabilistic safety assessment model that has been improved by a best-estimate safety analysis and a human reliability analysis, Martorell et al (2018) [129] suggested a three-step process to assess the risk impact of modifications to completion time within nuclear power plant technical specifications. The Vehicle Routing Problem (VRP) was examined by Jbili et al (2018) [130] in the context of unique transcontinental transportation scenarios in which large vehicles travel great distances between cities in challenging environments, increasing the likelihood that essential components may fail.…”
Section: Maintenance and Maintainabilitymentioning
confidence: 99%
“…Cheng et al (2018) [128] examined the combined issue of condition-based maintenance, quality control, and production lot size for an imperfect production system that is vulnerable to degradation in both reliability and quality. Using a probabilistic safety assessment model that has been improved by a best-estimate safety analysis and a human reliability analysis, Martorell et al (2018) [129] suggested a three-step process to assess the risk impact of modifications to completion time within nuclear power plant technical specifications. The Vehicle Routing Problem (VRP) was examined by Jbili et al (2018) [130] in the context of unique transcontinental transportation scenarios in which large vehicles travel great distances between cities in challenging environments, increasing the likelihood that essential components may fail.…”
Section: Maintenance and Maintainabilitymentioning
confidence: 99%
“…Human reliability refers to the probability that operators complete a task within the specified time in any stage of system operation [4]. As an emerging subject, the evaluation of human reliability aims to quantify and qualify the reliability of operators, making it possible to analyze, predict and reduce human error [5]. As stated by Kirwan [6], human reliability evaluation mainly derives the probability of accidents induced by human error, and finds the way to minimize human error.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La utilización de códigos BE permite descubrir nuevas secuencias accidentales no contempladas en el APS original y una cuantificación más realista de las PEH para las acciones involucradas en las mismas. El caso de aplicación presentado evalúa los cambios en la cuantificación de las PEH y el riesgo del cambio en el CT. Este capítulo amplía la investigación presentada en el artículo de P. Martorell et al (2018).…”
Section: Casounclassified